PERANCANGAN STRATEGI PEMASARAN BERDASARKAN PERILAKU KONSUMEN DARING PADA MULTI TOYS N GAME SURABAYA - Ronyastra, I Made; Damar, Vicio Rizky; Gunawan, Gunawan (Heuristic, 2017)
Multi Toys N Game is a store whose main business is selling action figures both offline and online. In order to win the competition, it needs a marketing strategies that should be based on the factors that can influence the customers. Using the online survey method combined with in-depth interview for data collection, the research revealed that characteristic of the buyer are male (86%), aged 19-24 (67%), student (60%), and with monthly expense of less than 3 million rupiah (71%). Most of the buyers are member of hobby community from where they are easily influenced in buying new action figures. 56% of the buyers actively using internet and social media on daily basis. The most popular product lines are nendoroid (51%), followed by gundam (48%). By using STPD and 8P method at lest there are three areas improvment: price positioning should use â€œmore for the sameâ€, product range availability should be improved by introducing new product line, and provide more payment process options by engaging with more major banks such as Mandiri, BNI, and BRI. Keywords: action figures, marketing strategies, consumer behaviour, online store